The kiler cat strikes back - Fine, Anne.; Cox, Steve, 1961- (London : Puffin Books, 2006)
Tuffy the pet cat tries to defend himself against accusations of terrifying other animals and murdering the neighbor's rabbit.
Publisher's Weekly
School Library Journal
Wilson's Children
3.3
K-3
K-3
Keywords: Cats -- Juvenile fiction; Cats -- Fiction; Cats -- Fiction